Aerosol light extinction and backscattering: A review with a lidar perspective. (March 2021) - Ceolato, Romain; Berg, Matthew J.
Highlights: Aerosol light extinction and backscattering are reviewed with a lidar perspective. The elastic lidar equation is derived from the radiative transfer equation. Extinction and backscattering cross-sections of aerosol particles are interpreted from wave-optics and phasor analysis. Digital holography and small-angle light-scattering methods are proposed for measuring the extinction properties of single aerosols. A new elastic backscatter short-range micro-lidar system, Colibri, is presented for measuring the backscattering properties of aerosol plumes. Abstract: Elastic backscatter lidar is an established method useful to characterize the particles forming an atmospheric aerosol. Fundamental to lidar measurements are the extinction and backscattering properties of the aerosol particles in the lidar beam. This review aims to give the reader an understanding for how lidar measurements are made, modeled, and applied. Specific emphasis is placed on extinction, which manifests attenuation of the lidar beam by the aerosol, and the backscattering that ultimately constitutes the measured signal. The so-called lidar equation, which quantifies this signal in terms of aerosol-particle properties, is derived from radiative transfer theory. Extinction is examined in terms of the redistribution of energy from the lidar beam by the particles and is shown to be inherently linked to interference between the incident and scattered light. Ways to measure aerosol-particle extinction are reviewed, including a recent method where the wave interference constitutes a digital hologram that may be processed to yield both the cross section and an image of the particle. The semi-graphical method of phasor analysis is also presented and used to reveal connections between the scattering characteristics of a particle and the distribution of electric field within it. Finally, a recently developed elastic backscatter lidar system, Colibri, is described and an example of its measurement capabilities are presented.